Behavioral Responses of Betta splendens to Environmental Factors - Archana P; Reemy Sara Mathai (The Bioscan, 2025)
Environmental conditions play a crucial role in shaping the behavioral patterns and overall welfare of aquarium fish species. This study examined the effects of three specific environmental factors—tank size, colored lighting, and sound exposure—on the behavior of male Betta splendens (Siamese fighting fish). Experiments were conducted under controlled indoor conditions, and behavioral responses were assessed based on swimming activity, exploration, hiding, resting, and aggression. Results indicated that larger tanks promoted natural and active behavior, while restricted spaces increased signs of stress such as hiding and inactivity. Lighting color significantly influenced aggression and exploratory patterns, with red light inducing more territorial behavior and blue light eliciting calmness and curiosity. Exposure to natural underwater sounds supported active behavior, whereas artificial piano music caused increased hiding and resting. These findings underscore the importance of optimizing captive environments for Betta splendens, both for enhancing welfare and maintaining natural behavior in ornamental settings.